HUBUNGAN KARAKTERISTIK DEMOGRAFI DENGAN TINGKAT STRES KERJA PADA PERAWAT PUSKESMAS KOTA DENPASAR DI MASA PANDEMI COVID-19 - Tustiani, Ni Ketut Nining Aras; Damayanti S, Made Rini; Damayanti, Putu Ayu Asri (Coping: Community of Publishing in Nursing, 2024)
Nurses played a role in preventing, detecting, and controlling Covid-19 during the Covid-19 pandemic. The high number of Covid-19 cases in Denpasar City has led to an increase in the roles and duties of nurses which can result in physical and mental workloads that trigger work stress. Nurse job stress is influenced by many factors, both external and internal factors. The purpose of this study was to determine the relationship between demographic characteristics and work stress levels among nurses in primary health care of Denpasar City during the Covid-19 pandemic. This study used an analytical cross-sectional method. Sampling in this study used a cluster random sampling technique with a total sample of 44 nurses. Data were collected using the Expanded Nursing Stress Scale (ENSS) questionnaire with chi-square statistical test. The results showed that the level of work stress experienced by nurses was high work stress 29,55%, moderate work stress 54,5%, and low work stress 15,9%. There was a significant relationship between age (p=0,000), marital status (p=0,000), education level (p=0,007), years of service (p=0,000), and working hours (p=0,000) with work stress. Meanwhile, gender demographic characteristics were not related to nurses' work stress level (p=0,368). The conclusion that majority nurses of primary health care in Denpasar City experience moderate levels of work stress and the characteristics of age, marital status, education level, years of service, and working hours are related to the occurrence of work stress in nurses in Denpasar City. Work stress must be handled holistically and comprehensively to obtain optimal work performance.